PEMBERDAYAAN KELOMPOK TANI SAWAH PAYO KABUPATEN TANAH DATAR MELALUI TEKNIK PEMANGKASAN TANAMAN KAKAO - Yulmira Yanti; Hasmiandy Hamid; Reflin Reflin; Noveriza Hermeria (Jurnal Hilirisasi IPTEKS, 2020)
Cocoa (Theobroma cacao L.) is one types of plantation plants that receive constant attention to develop. One of the areas in West Sumatra that emerged as the center of the cocoa plantation was nagari mount rajo, a flatland district. But in its cultivation, it often has the same problem that payo farm groups have in producing cocoa beans, cocoa trees that have aged and been destroyed by disease pests. An intensified effort to overcome the problem would be to reduce pests and disease attacks, and the cocoa production would continue to increase. The purpose of the farm group’s empowerment activity is to give knowledge of the techniques and processes of pruning good and proper cocoa cultivation plants according to the proper procedure in order to produce productivity results from the plant. The method used in this activity is a direct and indirect approach. A direct approach by conducting an interview with the nagari people of mount rajo and by socializing and live demonstrations in the field. The indirect method of doing this is observation. Observation is an observation made to know the habbit. The result of empowering activities is that communities especially payo farm groups have a greater knowledge of how to cultivate good and true cocoa plants, knowing when the time is right to do the pruning and the kind of pruning that is necessary so s to increase the production of the cocoa. This activity has been a tremendous help to the community in solving every problem found in the cultivation of the cocoa plant.